2017
DOI: 10.1242/dev.151951
|View full text |Cite
|
Sign up to set email alerts
|

Incompatibility between mitochondrial and nuclear genomes during oogenesis results in ovarian failure and embryonic lethality

Abstract: Mitochondrial dysfunction can cause female infertility. An important unresolved issue is the extent to which incompatibility between mitochondrial and nuclear genomes contributes to female infertility. It has previously been shown that a mitochondrial haplotype from D. simulans (simw 501) is incompatible with a nuclear genome from the D. melanogaster strain Oregon-R (OreR), resulting in impaired development, which was enhanced at higher temperature. This mitonuclear incompatibility is between alleles of the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 87 publications
(122 reference statements)
0
40
0
Order By: Relevance
“…; Zhang et al. ). Here, we show that the phenotypic expression of this genetic interaction is generally environment dependent and depends on intrinsic factors such as life stage and sex in a manner consistent with greater energy demands revealing fitness effects of mutations that compromise metabolism.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…; Zhang et al. ). Here, we show that the phenotypic expression of this genetic interaction is generally environment dependent and depends on intrinsic factors such as life stage and sex in a manner consistent with greater energy demands revealing fitness effects of mutations that compromise metabolism.…”
Section: Discussionmentioning
confidence: 98%
“…The fecundity defects in ( simw 501 ); OreR females are also strongly temperature dependent and involve defects in the development and maintenance of the ovary (Zhang et al. ). Furthermore, mothers of this genotype developed at 28°C produce defective eggs that have a lower probability of being fertilized and, when fertilized, die during embryogenesis presumably due to insufficient maternal provisioning or the inheritance of subfunctional mitochondria (Zhang et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In canonical mitochondria, incompatibilities between mitochondrial and nuclear DNA lead to cell death. For example, a mating combination with replacement of mitochondria results in embryonic death in mice (Ma et al 2016), and incompatibility between mitochondrial tRNA and aminoacyl tRNA synthetases encoded in nuclear DNA causes female infertility in Drosophila (Meiklejohn et al 2013;Zhang et al 2017). Sharpley et al (2012) showed that heteroplasmy of mitochondrial DNA leads to unexpected genetic and behavioral instabilities.…”
mentioning
confidence: 99%